Analysis of environmental impacts of drone delivery on an online shopping system - Jarotwan Koiwanit (My University, 2018)
In rural areas, drones are designed to replace road deliveries so as to overcome infrastructure challenges; though drones notably consume less fuel and consequently have a smaller impact on the environment, their full life cycle assessment should still be evaluated to comprehensively understand their environmental impact. This study presents a life cycle assessment study on drone delivery in Thailand using CML2001, the life cycle impact assessment (LCIA) method, to convert life cycle inventory data into environmental impacts. The observed results show that an online shopping system using drone delivery is one of the most environmentally friendly transportation options throughout a wide range of scenarios. However, the parts production contributed to significant impacts on environmental issues while the drone operation showed the least impact to all impact categories. The dominant contributors to global warming, abiotic depletion (ADP elements and fossil), acidification air, eutrophication, ozone layer depletion, and photochemical ozone creation impact categories were the coal mining and electricity generating station operation. However, the carbon fibers and the battery, are the main contributors to other impact categories, which include the human toxicity, freshwater aquatic ecotoxicity, marine aquatic ecotoxicity, and terrestric ecotoxicity.
Keywords: Ecotoxicity; Drone; Impact assessment; Inventory analysis; UAV Applications and Optimization